ANALISIS BIAYA DAN PENDAPATAN MANGGA GADUNG DI DESA BANDILAN KECAMATAN PRAJEKAN KABUPATEN BONDOWOSO - Obet Abu Priyono; Yuli Dwi Lestari; Rini Purwatiningsih (FORAGRI : Jurnal Ilmu Pertanian, 2023)
The use of the mango as a horticultural crop is becoming increasingly important to farmers due to its high economic value. Mango Gadung is a small part of the many mango varieties that are widely known and cultivated. Mango is one of the fruit crops that is good enough to be cultivated and in Bondowoso Regency mango is the third most important fruit commodity after jackfruit when viewed from the amount of production per year. This study used proportional random sampling and slovin techniques with survey and interview techniques and used primary and secondary data types. The data were processed using the farming cost and income analysis method which aims to determine the results of mango farming income and the constraints faced by farmers in Bandilan Village, Prajekan District, Bondowoso Regency.The average cost efficiency of gadung mango farming in Bandilan Village, Bondowoso Regency is 1.56, meaning that the use of farming costs is efficient because the value is greater than one. The R/C value of 1.56 indicates that every Rp.1,000,000 invested in the mango gadung farming business provides a yield of Rp. 1,566,666. Land area, pesticide costs, labor costs have a real effect on farmers’ income in gadung mango farming in Bandilan Village, Prajekan District, Bondowoso Regency.